LncRNA FOXC2-AS1 protects cardiomyocytes from doxorubicin-induced cardiotoxicity through activation of WNT1-inducible signaling pathway protein-1. Issue 4 (3rd April 2019) - Zhang, Shenwei; Yuan, Yiqiang; Zhang, Zheng; Guo, Jing; Li, Jing; Zhao, Kui; Qin, Yanping; Qiu, Chunguang
ABSTRACT: Doxorubicin (Dox) is an anthracycline antibiotic that has been used to treat different cancers. Dox-induced cardiotoxicity is common in clinical practice, while its mechanism is unknown. It has been proved that lncRNA FOXC2-AS1 may promote doxorubicin resistance and WNT1-inducible signaling pathway protein-1 (WISP1) blocks doxorubicin-induced cardiomyocyte death. Our study aimed to investigate the involvement of lncRNA FOXC2-AS1 and WISP1 in doxorubicin-induced cardiotoxicity and to explore their interactions. In our study we observed that FOXC2-AS1 and WISP1 mRNA were downregulated in heart tissues of mice with Dox-induced cardiotoxicity. FOXC2-AS1 and WISP1 mRNA expression were positively correlated in mice with Dox-induced cardiotoxicity but not in healthy mice. Overexpression of FOXC2-AS1 promoted to viability of mice cardiomyocytes under Dox treatment and also increased the expression level of WISP1. In contrast, WISP1 overexpression showed no significant effect on FOXC2-AS1. We therefore conclude that lncRNA FOXC2-AS1 may upregulate WISP1 to protect cardiomyocytes from doxorubicin-induced cardiotoxicity. Graphical abstract: : lncRNA FOXC2-AS1 may upregulate WISP1 to protect cardiomyocytes from doxorubicin-induced cardiotoxicity.